Lysolipids regulate raft size distribution - Krasnobaev, Vladimir D.; Galimzyanov, Timur R.; Akimov, Sergey A.; Batishchev, Oleg V. (Frontiers in Molecular Biosciences, 2022)
The lipid matrix of cellular membranes, directly and indirectly, regulates many vital functions of the cell. The diversity of lipids in membranes leads to the formation of ordered domains called rafts, which play a crucial role in signal transduction, protein sorting and other cellular processes. Rafts are believed to impact the development of different neurodegenerative diseases, such as Alzheimer’s, Parkinson’s, Huntington’s ones, amyotrophic lateral sclerosis, some types of cancer, etc. These diseases correlate with the change in the membrane lipid composition resulting from an oxidative stress, age-related processes, dysfunction of proteins, and many others. In particular, a lot of studies report a significant rise in the level of lysolipids. Physicochemical properties of rafts are determined by membrane composition, in particular, by the content of lysolipids. Lysolipids may thus regulate raft-involving processes. However, the exact mechanism of such regulation is unknown. Although studying rafts in vivo still seems to be rather complicated, liquid-ordered domains are well observed in model systems. In the present study, we used atomic force microscopy (AFM) to examine how lysophospholipids influence the liquid-ordered domains in model ternary membranes. We demonstrated that even a small amount of lysolipids in a membrane significantly impacts domain size depending on the saturation of the lysolipid hydrocarbon tails and the amount of cholesterol. The mixture with the bigger relative fraction of cholesterol was more susceptible to the action of lysolipids. This data helped us to generalize our previous theoretical model of the domain size regulation by lipids with particular molecular shape expanding it to the case of lysolipids and dioleoylglycerol.